Alpha-Lactalbumin improves sleep and recovery after simulated evening competition in female athletes - Miles, K. H.; Clark, B.; Fowler, P. M.; Gratwicke, M. J.; Martin, K.; Welvaert, M.; Miller, J.; Pumpa, K. L. (Medicine & Science in Sports & Exercise, 2021)
Purpose: This study aimed to determine the efficacy of a-lactalbumin (A-LAC) supplementation for improving sleep and performance recovery after simulated evening competition in female athletes. Methods: Sixteen trained women (mean ± SD: age, 27 ± 7 yr; mass, 62 ± 10 kg; stature, 167 ± 8 cm) participated in this randomized double-blind three-arm crossover study. Participants completed a simulated evening competition before consuming either an A-LAC whey protein, whey protein placebo (PLA), or water control (CON) beverage. Sleep was monitored via polysomnography, and participants completed a series of physical, cognitive, and perceptual assessments before, and 14 and 24 h after simulated competition. Results: Non-rapid eye movement stage 2 sleep increased after competition in A-LAC (pre, 199 ± 44 min; post, 212 ± 37 min) but decreased in CON (pre, 228 ± 43 min; post, 195 ± 40 min) and PLA (pre, 224 ± 25 min; post, 211 ± 35 min; P = 0.012). In addition, Yo-Yo Intermittent Recovery Test Level 1 distance improved over time in A-LAC (baseline, 664 ± 332 m; 14 h post, 667 ± 326 m; 24 h post, 781 ± 427 m) compared with CON (baseline, 741 ± 366 m; 14 h post, 648 ± 351 m; 24 h post, 720 ± 407 m) and PLA (baseline, 763 ± 394 m; 14 h post, 636 ± 366 m; 24 h post, 720 ± 396 m; P < 0.001). Conclusions: The findings indicate that A-LAC supplementation may be useful for retaining some sleep characteristics after evening competition, leading to improved physical performance in female athletes.